(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The effects of different packaging materials: plastic material, aluminium foil, glass material, low density polyethylene bag (LDPB) and a blend of plastic materials and LDPB on the keeping quality of kulikuli was studied. The quality indices studied were peroxide value, free fatty acid, saponification value and sensory attributes using standard methods. The results of the study showed that at the end of first week of storage, stored snacks exhibited different variabilities in the quality parameters measured. Snacks stored in foil paper and in a blend of plastic and LDPB had significantly (p<0.05) lower levels of quality indices measured. However, snacks stored in glass material and LDPB had higher values. At the end of the third week of storage, snack samples showed increased fatty acids, peroxide and saponification values which ranged from 8.97 – 13.46 mg/100 g, 12.40 – 13.40 meqO2/kg 84.15 – 44.80 mg KOH/g, respectively. Snacks stored in foil paper and in a blend of plastic and LDPB mantained lower levels of quality indices measured. Similarly, there were steady increase in free fatty acid, peroxide and saponification values of the snack samples with increasing storage time up to the seventh week of storage. Therefore, it can be deduced from this study that snacks stored in a blend of plastic and LDPB and foil paper alone up to three weeks maintained good product quality based on indices measured.